Resonant nano-dimer metasurface for ultra-thin a-Si:H solar cells - Mahmoud H. Elshorbagy (Nature Portfolio, 2021)
Abstract Low-cost hydrogenated amorphous silicon solar cells (a-Si:H) can perform better and be more competitive by including nanostructures. An optimized nano-dimer structure embedded in close contact with the back electrode of an aSi:H ultra-thin solar cells can enhance the deliverable short-circuit current up to 27.5 %. This enhancement is the result of an increase in the absorption at the active layer, that is the product of an efficient scattering from the nanostructure. From our calculations, the nano-dimer structure must be made out of a high-index of refraction material, like GaP. The evaluation of the scattering and absorption cross section of the structure supports the calculated enhancement in short-circuit current, that is always accompanied by a decrease in the total reflectance of the cell, which is reduced by about 50 %.